On Raman spectra of water, its structure and dependence on temperature - Baschenko, S.M.; Marchenko, I.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
Raman spectra of water within the temperature range 20 to 3 C were investigated. Best of all, the complex shape of the obtained spectra was approximated by four (or five) Gaussian-shaped peaks with their positions 3070, 3230, 3440, 3600 (and 3650) cm⁻¹. The most intensive constituents were 3230 and 3440 cm⁻¹ lines, their total contribution to the Raman spectrum of water is higher than 90%. These lines are the most sensitive to the temperature, too. When the temperature decreases from 20 down to 3 C, the positions of these peaks were shifted from 3232 to 3224 cm⁻¹ and from 3441 to 3434 cm⁻¹, respectively; and the intensity of 3230 cm–1 line was increased approximately by 14% in its magnitude